Pengaruh model pembelajaran dan kemampuan awal terhadap kemampuan berpikir kritis dan pemahaman konsep peserta didik - Muhammad Danial; Tabrani Gani; Husnaeni Husnaeni (Journal of Educational Science and Technology (EST), 2017)
which was taught by guided inquiry learning model with the learners who learned the learning discovery learning model. (2) differences in the ability to understand the concepts of learners who are taught by guided inquiry learning model with learners who are taught by the learning model of discovery learning. (3) differences in the critical thinking ability of learners who have high initial ability and low initial ability are taught by guided inquiry learning model with learners who are taught by discovery learning learning model. (4) the difference in the ability of conceptual understanding between learners who have high initial ability and low initial ability that is taught by guided inquiry learning model with learners who are taught by discovery learning learning model. (5) the difference between the critical thinking ability of learners with high initial ability and low initial ability which is taught by guided inquiry learning model and discovery learning. (6) the difference between the difference in the understanding of high-ability early-skilled learners and low initial skills learned by guided inquiry learning and discovery learning models. Research is a quasi-experimental research (quasi experiment). The results of the research are: (1) There are differences of learning model to the critical thinking ability of learners; (2) There are differences of learning model to; (3) There is a difference of students' early ability to critical thinking ability of learners; (4) There is a difference in the learner's early ability to understand the concept of the learner; (5) There is a difference between the difference in the critical thinking ability of learners with high initial ability and low initial ability taught by the learning model; (6) There is a difference between the difference in understanding the concept of learners with high initial ability and low initial ability learned by the learning model.